Preliminary Thermo-Mechanical Assessment of a Pneumatically Actuated Permanent-Mold Gravity-Casting Apparatus - Nur Wahid Panji Anggoro; Sutimin Sutimin; Bagus Wicaksono (Akademi Inovasi Indonesia, 2026)
Low-cost automation of permanent-mold gravity casting requires adequate actuator capacity, guide stiffness, and accommodation of differential thermal growth. This study presents a preliminary analytical assessment of a compact, pneumatically actuated permanent-mold gravity-casting apparatus. The assessment uses documented geometry and conservative screening assumptions for a 100 mm-bore double-acting cylinder at 0.60 MPa, a 25 mm piston rod, two 40 mm S45C guide shafts over a 0.60 m span, locally procured bronze sleeve bushings, and a ferrous mold plate that is 40 mm thick with a 0.40 m axial characteristic length. For horizontal translation, the force model excludes the full assembly weight from the cylinder-axis resistance and includes guide friction (μ = 0.15), 100 N ejector-spring resistance, a 200 N unmeasured process allowance, and a design factor of 2. The resulting factored demand is 0.748 kN. The extension and retraction load ratios are 0.159 and 0.169 relative to theoretical cylinder output, below the 0.50 guideline used for dynamic cylinder selection. The idealized guide-shaft model predicts 0.045 mm deflection and 5.97 MPa bending stress. Nominal thermal growth is 1.20 mm for the 0.40 m mold dimension and 0.44 mm for the 0.80 m rail length under assumed temperature rises, leaving a nominal 0.80 mm margin against a 2.0 mm drawing allowance before tolerance effects. Because the mold grade, bronze alloy, as-built clearance, stroke history, and trial-cycle data were not documented, no durability, measured-alignment, or material-specific PV-compliance claim is made. The contribution is an integrated and explicitly bounded force-stiffness-thermal screening framework for low-cost casting apparatuses.